2019
DOI: 10.1038/s41598-019-43608-6
|View full text |Cite
|
Sign up to set email alerts
|

Calcium phosphate mineralization in bone tissues directly observed in aqueous liquid by atmospheric SEM (ASEM) without staining: microfluidics crystallization chamber and immuno-EM

Abstract: The malformation and disordered remodeling of bones induce various diseases, including osteoporosis. We have developed atmospheric SEM (ASEM) to directly observe aldehyde-fixed bone tissue immersed in radical scavenger buffer without thin sectioning. The short procedure realized the observation of bone mineralization surrounded by many cells and matrices in natural aqueous buffer, decreasing the risk of changes. In osteoblast primary cultures, mineralization was visible without staining. Correlative energy dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 44 publications
1
13
1
Order By: Relevance
“…Intriguingly, we found that osteoblasts protrude podia to the bone matrix at extremities of the developing frontal bone (Figure 5D). A similar structure was briefly observed in osteoblasts in a cortical bone of the mouse tibia 69 , yet the detailed structure remains undescribed. Since all osteoblasts on the surface of the bone matrix possess podia connecting to the bone matrix, these podia potentially have critical functions in bone development, such as supplying phosphate or calcium, one of the main functions of osteoblasts during ossification 70 .…”
Section: Discussionsupporting
confidence: 54%
“…Intriguingly, we found that osteoblasts protrude podia to the bone matrix at extremities of the developing frontal bone (Figure 5D). A similar structure was briefly observed in osteoblasts in a cortical bone of the mouse tibia 69 , yet the detailed structure remains undescribed. Since all osteoblasts on the surface of the bone matrix possess podia connecting to the bone matrix, these podia potentially have critical functions in bone development, such as supplying phosphate or calcium, one of the main functions of osteoblasts during ossification 70 .…”
Section: Discussionsupporting
confidence: 54%
“…The block was inverted and placed on the SiN film forming the window of the ASEM dish so that the top of the biofilm was in direct contact with the SiN film. The biofilm was immersed in radical scavenger glucose solution 42 and immediately imaged by optical microscopy and SEM 43 . The electron dose at the highest magnification of 20,000 × was 2.5 e - /Å 2 , which is 5.3% of the dose of 47 e - /Å 2 permitted in low-dose cryo-electron microscopy aiming at atomic resolution single particle reconstructions.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the thick fiber-containing EPM might include double-stranded DNA filaments and extracellular polysaccharides, as observed in the biofilms of S. aureus and P. acnes immersed in aqueous liquid by atmospheric scanning electron microscopy (ASEM) [45,46]. Further experiments are required to understand the water-rich architecture of F. johnsoniae biofilms, for example, using ASEM that enabled observations of various water-rich phenomena of organic and inorganic substances at high resolution [16,51,52]. The undulations observed for the layered surface coats of F. johnsoniae cells in biofilm has a possibility to be artefacts, due to the dehydration pretreatment of the Epon-embedded TEM.…”
Section: Discussionmentioning
confidence: 99%